A scoping review of interventions for vaccine stock management in primary health-care facilities - Chinwe Juliana Iwu; Anelisa Jaca; Leila Hussein Abdullahi; Ntombenhle Judith Ngcobo; Charles Shey Wiysonge (Taylor & Francis Group, 2019)
One of the challenges facing the success of immunization programs is shortages of vaccines at health facilities, which could result from inadequate vaccine stock management. Several approaches have been designed by countries to improve vaccine stock management. This review summarizes currently available information on interventions for vaccine stock management. We considered both randomized trials and non-randomized studies eligible for inclusion in this review. The following databases were searched: PubMed, Embase, Cochrane Central Register of Controlled Trials, World Health Organization Library Information System, Web of Science, and PDQ-Evidence. We searched the websites of the World Health Organization, Global Alliance for Vaccine and Immunization, PATH's Vaccine Resources Library, and United Nations Children's Fund. The reference lists of all the included studies were also searched. Two authors independently screened search outputs, reviewed full texts of potentially eligible articles, evaluated risk of bias, and extracted data; resolving disagreements through consensus. Four studies met our inclusion criteria (three before-after studies and one randomized trial). Three studies were conducted in low- and middle-income countries while one was conducted in Canada (a high-income country). All the studies had various limitations and were classified as having a high risk of bias. Study findings suggest that the use of digital information systems to improve information and stock visibility, coupled with other interventions (such as training of health-care workers on the use of innovative tools and redesign of the supply chain to tackle certain bottlenecks), has the potential to increase vaccine availability, reduce response times, and improve the quality of vaccine records.